Development of a four–speed automatic transmission with overdrive. (5th August 2014) - Numazawa, A.; Kubot, S.; Shindo, Y.; Moroto, S.
A new four–speed automatic transmission with overdrive has been developed and put into production for the purpose of improvement of fuel economy and the reduction of engine noise. The transmission has the following characteristics: gear train arrangement with overdrive unit; lower overdrive gear ratio; shift feel controls for clutch–to–clutch shifting; optimum shift points on fuel economy, driveability and exhaust emissions; lockout system of overdrive gear. For optimum gear ratios, shift points, and smooth shift feel controls, computer simulations were used to provide design direction. This paper describes the design features and the confirmation testings of the transmission, and also refers to effects on fuel economy and noise reduction of the transmission in the vehicle.